Pengenalan Kurikulum Merdeka Belajar Kepada Peserta Didik di SD Mutiara Indah - Rezeki Putra Gulo; Sariani Hia; Erwin Zai (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This PkM activity was held at Mutiara Indah Elementary School, Kualeu Village, Oinlase District, East Tengah Selatan District, So'e City. The method used is a field survey and library research. The PkM activities carried out were an attempt to